Traducción y adaptación de la Escala de Depresión Reynolds para niños en una muestra puertorriqueña (Revista Puertorriqueña de Psicologia, 2016)
In this study was performed a translation of the Reynolds Child Depression Scale - RCDS (Reynolds, 1989), to count with a valid and reliable self-report instrument on the signs and symptoms of depression in children from 8-12 years. The study evaluated the internal and the concurrent validity with the Child Depression Inventory - CDI (kovacs, 1983), in a clinical and community sample in Puerto Rico. the clinical sample consisted of 43 participants of whom 60% were male between 8 and 13 years of age, from mainly public schools, receiving psychological or psychiatric treatment, in a San Juan mental health center. The community sample (children who never received psychological or psychiatric treatment), consisted of 90 participants of whom 63% were females between 8 an 13 years of age, from a private school.